Does Reputation Matter? Investigating the Mediating Link between Corporate Responsibilities, Governance and Financial Performance - RIA MENNITA; CITRA SARASMITHA; PUJANGGA ABDILLAH; HILARIA ANAEMA; Shada Syahirah (Fakultas Ekonomi Universitas Kadiri, 2026)
The digital transformation and rising global sustainability demands, pushed telecommunication companies invest heavily in social and governance aspects to maintain their market positioning; however, the effectiveness of these investments is often questioned as governance practices are frequently dismissed as mere administrative formalities. This study aims to examine the impact of Corporate Social Responsibility (CSR) and Corporate Governance on financial performance, with corporate reputation as a mediating variable. Utilizing purposive sampling, secondary data from telecommunication companies listed on the stock exchange for the 2021–2024 period were analyzed using mediation regression analysis. The results indicate that CSR consistently enhances both financial performance and corporate reputation within the telecommunications sector, proving tangible economic returns. Conversely, Corporate Governance has no significant impact on either, indicating that governance implementation remains strictly compliance-driven. Furthermore, strong financial performance is proven to be the foundational pillar for building market reputation. Finally, corporate reputation fails to mediate the relationship between CSR, governance and financial performance; the financial benefits of CSR are direct driven by operational efficiency and legal compliance, confirming that investors prioritize concrete business outcomes over abstract image-building.